Pathways into teacher education : profiles of emerging teacher educator development - Butler, Brandon M.; Cuenca, Alexander, 1979-; Ritter, Jason K.; Yendol-Hoppey, Diane; Hoppey, David (Emerald Publishing Limited : IAP | Information Age Publishing Inc., 2023)
"Teacher educator learning has received increasing attention in recent decades. Although the professional development needs of teacher educators has become more visible, the spaces where teacher educators learn to teach teachers is less clear. How do teacher educators learn? What do they learn? And where does this learning take place? This edited volume provides answers to these questions through an unpacking of the programs, courses, and professional learning spaces in which beginning teacher educators learn. In this edited volume, chapters provide profiles, or "cases," of the spaces in which beginning university-based teacher educators are prepared. University-based teacher educator learning occurs in a range of settings. As highlighted in this volume, such learning spaces include doctoral program concentrations or minors focused on the development of teacher educator identity and practice; individual doctoral courses dedicated to teacher education; formalized program experiences that assist in the preparation of teacher educators; and mentoring or critical friendship collaborations through which doctoral students learn about teacher education with peers or from experienced teacher educators"-- Provided by publisher.
Keywords: Teachers -- Training of.; Teachers -- Training of -- Research.; Teachers -- In-service training.; Teachers -- In-service training -- Research.; Teaching -- Methodology.; Teacher educators -- Professional relationships.; Education -- Teacher Training & Certification.; Teacher training.; elektronické knihy; electronic books